1914
DOI: 10.6028/bulletin.238
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the silver and iodine voltameters and the determination of the Faraday

Abstract: Chemicals and solutions 429 3. Methods of standardization and analysis 431 4. vStrength of the standard arsenious acid solution 435 B. The silver voltameters 437 1. Forms used 437 2. Materials, eic 437 IV. Tables of results 438 V. Discussion of results

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

1924
1924
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 0 publications
1
12
0
1
Order By: Relevance
“…However, 4 years earlier (in 1912) Washburn and Bates [ 3 ] had proposed an improved 2 iodine coulometer for which high reproducibility and accuracy were claimed. In 1914 Vinal and Bates [ 8 , 9 ] made a direct comparison of the silver and iodine coulometers in the laboratories of NBS and found that the two methods yielded different values for the faraday. Since the two types of coulometers were run in series the ratio of the results given by the two methods was independent of the electrical units and the durations of the runs.…”
Section: Introductionmentioning
confidence: 99%
“…However, 4 years earlier (in 1912) Washburn and Bates [ 3 ] had proposed an improved 2 iodine coulometer for which high reproducibility and accuracy were claimed. In 1914 Vinal and Bates [ 8 , 9 ] made a direct comparison of the silver and iodine coulometers in the laboratories of NBS and found that the two methods yielded different values for the faraday. Since the two types of coulometers were run in series the ratio of the results given by the two methods was independent of the electrical units and the durations of the runs.…”
Section: Introductionmentioning
confidence: 99%
“…Silver dissolution e,f based on the relation 1 NBS ampere = 1.000012 absolute ampere based on the relation 1 NBS ampere = 1.000011 absolute ampere based on the silver/iodide weight ratio [24,25] based on coulombs used to liberate iodine [24,25] based only on the vacuum values of Craig, Hoffman, Law, and Hamer [28] f using 107.8685 for the atomic weight of silver s value recommended by the National Academy of Sciences-National Research Council [23] calculated on the basis of the coulometric titration of ASpCU with electrogenerated iodine reported in [21] x values obtained in this work. 55 Accordingly, one must use the faraday on the "NBS" (legal) basis (96485.8 NBS C/g-equiv) .…”
Section: Analysis For Lead In Lead-tin-telluridementioning
confidence: 99%
“…After storing in a desiccator over phosphorous pentoxide for about 24 hours, samples weighing about 0.27 g were ashed slowly to 500°C.…”
Section: Analysis Of Lead and Zinc Cyclohexanebutyratesmentioning
confidence: 99%
“…In 19 16 Vinal and Bates [22,23 ] made a direc t co mpari so n of th e silve r a nd iodin e co ulom e te rs in th e la bora tori es of NBS . Th e silv er co ulome ter was used .. to es ta bli sh th e c harge in internati onal units and in 6 of 10 expe rim e nts th e inte rn a ti ona l co ul o mb s we re de termin ed direc tl y fro m th e dura ti on of th e run a nd > va lu es of s ta nd ard cell s a nd s ta nd a rd res is tors kn own in inte rn ati onal units.…”
Section: Iodide Oxidation Methodsmentioning
confidence: 99%